Research progress on the structural characteristics of nanobodies and their applications in the treatment of infectious diseases - Xin ZHANG; Ruixin DENG; Jianqing LIU (Zhongguo gonggong weisheng, 2024)
Pathogenic microorganisms can cause a variety of infectious diseases. In recent years, large-scale outbreaks of infectious diseases such as Ebola hemorrhagic fever, COVID-19 infection, and malaria have prompted people to seek more concise and effective methods to treat severe infectious diseases. Nanobodies are VHH domains discovered on heavy-chain antibodies found in camel serum. With a molecular weight as low as 12-15 kDa, they are only 1/10 the size of traditional antibodies and are the smallest functional single-domain antibodies that can stably bind to antigens. Due to their small molecular size, strong tissue penetration, high specific affinity, ability to recognize epitopes in crevices, low immunogenicity, high water solubility, strong stability, simple production, and ease of expression, nanobodies have become a new type of antibody that can meet various research, diagnostic, and therapeutic requirements. This article introduced the structure and characteristics of nanobodies, and outlines their application progress in the treatment of infectious diseases, providing a reference for future development and research.